🎉 从330转为WashU帮助手册啦!

Math429
模块
Math429 L3

Lecture 3

Chapter I Vector Spaces

Subspaces 1C

Given a vector space VV, a subset WVW\subset V is called a subspace if

{WϕW is closed under addition and scalar multiplication\begin{cases} W\neq \phi\\ W\textup{ is closed under addition and scalar multiplication} \end{cases}

Definition 1.41

Direct Sum

Suppose V1,...,VmV_1,...,V_m are subspace of VV. Their sum V1+...+VmV_1+...+V_m is called a direct sum if each element v1+...+vmV1+...+Vm\vec{v_1}+...+\vec{v_m}\in V_1+...+V_m in a unique way.

If v1+....+vmv_1+....+v_m is a direct sum, we write it as

v1v2...vmv_1\oplus v_2\oplus ...\oplus v_m

Example:

V=R3V=\mathbb{R}^3

V1={(x,y,0):x,yR}V2={(0,a,b):a,bR}V_1=\{(x,y,0):x,y\in \mathbb{R}\}\\ V_2=\{(0,a,b):a,b\in \mathbb{R}\}

Is V1+V2V_1+V_2 a direct sum?

No, because there are other ways to build (0,0,0) in such space, which is not unique

For vector (0,0,0)=(x,y,0)+(0,a,b)(0,0,0)=(x,y,0)+(0,a,b), as long as y=ay=-a, there are other ways to build up the vector.

Theorem 1.45

Suppose V1,...,VmV_1,...,V_m are subspaces of VV, then V1+...+VmV_1+...+V_m is a direct sum if and only if the only way to write 0=v1+...+vm\vec{0}=\vec{v_1}+...+\vec{v_m} with v1V1,...,vmVm\vec{v_1}\in V_1,...,\vec{v_m}\in V_m. is v1=...=vm=0\vec{v_1}=...=\vec{v_m}=\vec{0}

Proof:

\Rightarrow

If v1=...=vm\vec{v_1}=...=\vec{v_m} is a direct sum, then the only way to write 0=v1+...+vm\vec{0}=\vec{v_1}+...+\vec{v_m} where viVi\vec{v_i}\in V_i is 0=0+...+0\vec{0}=\vec{0}+...+\vec{0} follows from the definition of direct sum

\Leftarrow

Need to show if the property holds for 0\vec{0}, then it holds for any vV1+...+Vm\vec{v}\in V_1+...+V_m     \iff If the property fails for any vV1+...+Vm\vec{v}\in V_1+...+V_m, then it fails for 0\vec{0}

If a vector vV1+...+Vm\vec{v}\in V_1+...+V_m satisfies v=v1+v2+...+vm=u1+u2+...+um\vec{v}=\vec{v_1}+\vec{v_2}+...+\vec{v_m}=\vec{u_1}+\vec{u_2}+...+\vec{u_m}, vi,uiVi\vec{v_i},\vec{u_i}\in V_i and there exists i{1,...,m}viuii\in\{1,...,m\}\vec{v_i}\neq \vec{u_i},

then (v1+v2+...+vm)(u1+u2+...+um)=0(\vec{v_1}+\vec{v_2}+...+\vec{v_m})-(\vec{u_1}+\vec{u_2}+...+\vec{u_m})=\vec{0}